Efficient ultrafast laser writing with elliptical polarization - Yuhao Lei; Gholamreza Shayeganrad; Huijun Wang; Masaaki Sakakura; Yanhao Yu; Lei Wang; Dmitrii Kliukin; Linards Skuja; Yuri Svirko; Peter G. Kazansky (Light: Science & Applications, 2023)
Efficient creation of anisotropic nanopores and associated birefringence in fused silica by elliptically polarized femtosecond laser pulses is observed. Applications in multiplexed optical data storage and optical elements are demonstrated.